Analysis of Phytochemical and Antioxidant Variation between Selected Phenophase of Raphanus sativus L. leaves (International Journal of Scientific Research in Science and Technology, 2025)
The present study explores the Phytochemicals and Antioxidant activity variation between distinct phenophases, namely large leaves and microgreens, of Raphanus sativus L. Utilizing methanol and acetone solvents with spectrophotometric assays, we characterized the phytochemical profile of both Phenophases. Results revealed significant variations in phytochemical constituents in rich array of compounds including Phenol, Flavonoid, Carbohydrate, Saponin, Coumarin, Diterpene and Terpenoid. Notably absent were Alkaloids, Protein, Glycosides, Terpenes and lignin in any of the analyzed samples. Furthermore, our research delves that Microgreens and leaves have the highest TPC Concentration 5.19 ± 0.02 mg GAE/g and 4.91 ± 0.07 mg GAE/g in Acetone solvent respectively. The TFC concentration in Leaves with Acetone 0.72 ± 0.13 mg QE/g is maximum. Additionally, antioxidant potential was assessed through DPPH scavenging activity, it indicates that methanolic extracts exhibited greater antioxidant activity compared to acetone extracts, as evident by lower IC50 values indicating higher efficacy in neutralizing DPPH radicals. These findings underscore the importance of considering phenological stages in exploiting the nutritional and therapeutic potential of this agriculturally significant plant species.